Medical Activity in the Conventional Hospitalization Unit in Kabul NATO Role 3 Hospital: A 3-Month-Long Experience. Issue 2 (1st February 2014) - Brondex, Aurore; Viant, Eric; Trendel, Dominique; Puidupin, Marc
ABSTRACT: Introduction: The main goal of the North Atlantic Treaty Organization role 3 hospital located in Kabul is to provide comprehensive medical services to troops engaged in Afghanistan. Nevertheless, it also provides care for Afghan National Security Forces and for Afghan and non-Afghan civilians. Objectives: To describe the patients admitted to the conventional hospitalization unit over a 3-month period, between June 29 and October 1, 2012. Results: A total of 439 patients were admitted, for scheduled surgery, discharged from intensive care unit, or referred by emergency room and primary care physicians. Causes of hospitalization were diverse, particularly for nonscheduled admissions, with mainly war- and traffic-accident-related injuries for Afghan civilians and national security forces, and non-war- and non-traffic-accident-related trauma emergencies and gastroenteritis for non-Afghan patients. Suspected or confirmed cardiovascular diseases were a frequent cause of hospitalization and the leading cause of medical evacuation out of war zone for non-Afghan civilians. The patients admitted for war injuries were mainly Afghan civilians, of whom 36.6% were children and 44.7% had been injured by improvised explosive devices. Conclusion: Reasons of admission to the conventional hospitalization unit were numerous. Care provided to Afghan and non-Afghan civilians represented the main activity of this unit.